La participación de los jóvenes en los movimientos políticos del cantón Loja, periodo 2021-2022 - Méndez Paladines, Anggie Yolanda (2024)
The purpose of the present investigation is to determine the level of participation of young people within the political movements of the Loja canton, for which the period 2021- 2022 is taken as empirical evidence. Within this study, conditions associated with equality through inclusion were considered, observed according to political movements, numbers of affiliates, those elements that help determine the conditions under which the participation of young people in political movements occurs The methodology applied in this research had a qualitative approach, applied to a database provided by the CNE, and interviews directed at people who know about the subject, such as the leaders of political organizations. Among the main results obtained, it is determined that there is a low level of participation of young people in political movements, the same that is located at 24% in relation to all the movements studied, this condition becomes more evident when analyzing the role they have within the directives of the political movements of the Loja canton, since it is possible to identify that the majority of young people who are active in political organizations do not hold decision-making or managerial positions.